Alternativas sostenibles para el control del oidio de la vid (Oidium tuckeri) - Arias, Maria Fernanda; D'innocenzo, Sandra Haydeé; Turaglio, María Eugenia; Navarro, Rosanna Graciela (Asociacion Argentina de Fitopatologia, 2022)
Poster